2007
DOI: 10.1021/ja066930l
|View full text |Cite
|
Sign up to set email alerts
|

Aryl-Fluoride Reductive Elimination from Pd(II):  Feasibility Assessment from Theory and Experiment

Abstract: DFT methods were used to elucidate features of coordination environment of Pd(II) that could enable Ar-F reductive elimination as an elementary C-F bond-forming reaction potentially amenable to integration into catalytic cycles for synthesis of organofluorine compounds with benign stoichiometric sources of F(-). Three-coordinate T-shaped geometry of Pd(II)Ar(F)L (L = NHC, PR(3)) was shown to offer kinetics and thermodynamics of Ar-F elimination largely compatible with synthetic applications, whereas coordinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
124
1
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(140 citation statements)
references
References 111 publications
5
124
1
10
Order By: Relevance
“…[11][12][13] Besondere Aufmerksamkeit auf diesem Forschungsgebiet erhielten die C-H-Funktionalisierungen, die über Pd II /Pd IV -Katalyse verlaufen. [13] Jüngste Untersuchungen der C-H-Funktionalisierungen lieferten eine Reihe neuer Oxidationsmittel, die eine reduktive Eliminierung durch die Oxidation von Pd II -zu energiereicheren Pd [17] Die Effektivität von F + -Oxidationsmitteln hat ihre Ursache im Widerstreben metallischer Spezies, reduktive Kohlenstoff-Fluor(C-F-)Eliminierungen einzugehen, [18,19] [11a-c, 13a] und bereiteten den Weg für diverse weitere, jüngere Pd II -katalysierte C-H-Halogenierungen, von denen sowohl wir [13b, 21] als auch andere Gruppen [13a, 22] berichteten, einschließlich einer asymmetrischen Variante, für die ein abtrennbares chirales Hilfsmolekül, das in unserem Labor entwickelt wurde, verwendet wurde (Schema 4). [13b, 23] Die Fluorierung erwies sich hauptsächlich aus zwei Gründen als problematischer als andere C-H-Halogenierungen: Erstens enthalten elektrophile F + -Reagentien [24] häufig chelatbildende Gruppen, die mit Pd II als starke s-Donor-Liganden agieren und damit den Schritt der C-H-Spaltung behindern können.…”
Section: Introductionunclassified
“…[11][12][13] Besondere Aufmerksamkeit auf diesem Forschungsgebiet erhielten die C-H-Funktionalisierungen, die über Pd II /Pd IV -Katalyse verlaufen. [13] Jüngste Untersuchungen der C-H-Funktionalisierungen lieferten eine Reihe neuer Oxidationsmittel, die eine reduktive Eliminierung durch die Oxidation von Pd II -zu energiereicheren Pd [17] Die Effektivität von F + -Oxidationsmitteln hat ihre Ursache im Widerstreben metallischer Spezies, reduktive Kohlenstoff-Fluor(C-F-)Eliminierungen einzugehen, [18,19] [11a-c, 13a] und bereiteten den Weg für diverse weitere, jüngere Pd II -katalysierte C-H-Halogenierungen, von denen sowohl wir [13b, 21] als auch andere Gruppen [13a, 22] berichteten, einschließlich einer asymmetrischen Variante, für die ein abtrennbares chirales Hilfsmolekül, das in unserem Labor entwickelt wurde, verwendet wurde (Schema 4). [13b, 23] Die Fluorierung erwies sich hauptsächlich aus zwei Gründen als problematischer als andere C-H-Halogenierungen: Erstens enthalten elektrophile F + -Reagentien [24] häufig chelatbildende Gruppen, die mit Pd II als starke s-Donor-Liganden agieren und damit den Schritt der C-H-Spaltung behindern können.…”
Section: Introductionunclassified
“…In fact, a carbon-fluorine bond formation to form an aryl fluoride by concerted aryl-fluorine reductive elimination from a well-defined transition metal fluoride, while implicated, 8 has not been substantiated in the literature from any transition metal in any oxidation state. 8,9 Scheme 1 shows a reaction sequence to convert a boronic acid into the corresponding arylfluoride. We found that pyridylsulfonamide ligands such as 2 are well suited for the fluorination reaction, because they serve as ancillary ligands to support arylpalladium complexes such as 5, which afford arylfluorides regiospecifically upon treatment with Selectfluor™ in high yield (87% in the presented case).…”
mentioning
confidence: 99%
“…[15,16] Carbon-fluorine bond formation to form aryl fluorides by reductive elimination from a Pd (II) fluoride complex has not yet been substantiated. [16,17] In general, all methods mentioned above cannot be employed for late-stage fluorination of structurally complex molecules due to either harsh reaction conditions or limited substrate scope. We have sought a new regiospecific, late-stage fluorination reaction of arenes that encompasses a larger substrate scope than currently accessible, tolerates the presence of a variety of functional groups, is not limited to a particular class of arenes, and is not dependent on a directing group.…”
mentioning
confidence: 99%